2023
DOI: 10.22541/essoar.168881869.96894704/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Uncertainty in Water Vapor Continuum Absorption on CO2 Forcing, Longwave Feedback, and Climate Sensitivity

Abstract: We assess the effect of uncertainty in water vapor continuum absorption on radiative forcing F, longwave feedback λ, and climate sensitivity S at surface temperatures Ts between 270K and 330K. We calculate this uncertainty using a line-by-line radiative-transfer model, assuming moist-adiabatic temperature profiles, 80% relative humidity, and spectrally uniform variations in continuum absorption of ±10%. At Ts=288 K this uncertainty translates to uncertainties of ±0.02Wm−2 (±0.5%) in F and ±0.04Wm−2K−1 (±2.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
(105 reference statements)
0
0
0
Order By: Relevance
“…Our analysis is based on the konrad model version 1.0.1 (available at https://doi.org/10.5281/zenodo.6046423, Kluft et al, 2022), with some modifications to the model to support the scaling of absorption species (available at https://doi.org/10.5281/zenodo.10961148, Roemer et al, 2024a). For the radiative transfer simulations, we use the ARTS model version 2.6.2 (available at https://doi.org/10.5281/zenodo.10868342, Buehler et al, 2024).…”
Section: Appendix A: Sensitivity To Idealizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis is based on the konrad model version 1.0.1 (available at https://doi.org/10.5281/zenodo.6046423, Kluft et al, 2022), with some modifications to the model to support the scaling of absorption species (available at https://doi.org/10.5281/zenodo.10961148, Roemer et al, 2024a). For the radiative transfer simulations, we use the ARTS model version 2.6.2 (available at https://doi.org/10.5281/zenodo.10868342, Buehler et al, 2024).…”
Section: Appendix A: Sensitivity To Idealizationsmentioning
confidence: 99%
“…The model output produced in this study can be found at https://doi.org/10.5281/zenodo.10963838 (Roemer et al, 2024c), the code needed to run the models and produce the figures of this study can be found at https://doi. org/10.5281/zenodo.10963797 (Roemer et al, 2024b).…”
Section: Appendix A: Sensitivity To Idealizationsmentioning
confidence: 99%
See 1 more Smart Citation